Cryptic diversity in Brazilian endemic monkey frogs (Hylidae, Phyllomedusinae, Pithecopus) revealed by multispecies coalescent and integrative approaches - Silva Ramos, Elisa Karen; Magalhaes, Rafael Felix de; Santos Marques, Nubia Carla; Baeta, Delio [UNESP]; Anchietta Garcia, Paulo Christiano; Santos, Fabricio Rodrigues (Elsevier B.V., 2019)
Even though Brazil is the world leader in amphibian diversity, a significant part of its richness remains unknown or hidden under cryptic taxa. Here, we used model-based species delimitation in an integrative taxonomic approach, by gathering molecular and morphometric data to assess cryptic taxa within the monkey frogs Pithecopus rohdei, from the Atlantic Forest, and P. megacephalus, from campos rupestres ecosystem. We sampled one mitochondrial, five nuclear loci, and 18 morphometric variables. Using species-delimitation methods with genetic and morphometric data, we recovered five divergent lineages within P. rohdei and no cryptic lineages were recovered for P. megacephalus. Morphometric data show differentiation only for one of the candidate species revealed by the delimitation approaches, suggesting that individuals from Doce River basin constitute a putative species for formal taxonomic description. The time-calibrated mtDNA tree shows that P. rohdei complex lineages began to diverge in late Miocene. However, dates from the multilocus species tree are more recent, occurring in Pleistocene, and suggesting their persistence in refuges of forest and sky islands within the Atlantic Forest biome. The existence of cryptic taxa within P. rohdei is, therefore, relevant for planning conservation strategies for this species complex in the Atlantic Forest biodiversity hotspot.
Keywords: Bayesian species delimitation; Atlantic Forest; Campos rupestres; Conservation; Pithecopus rohdei; Pithecopus megacephalus